Rivers and beaver-related restoration in Colorado - Scamardo, Julianne, author; Wohl, Ellen, advisor; Covino, Tim, committee member; Morrison, Ryan, committee member (Colorado State University. Libraries, 2019)
Reintroducing North American beaver (Castor canadensis) to streams within their historic range can restore aquatic and riparian habitat where historic beaver loss has initiated degradation. Determining where beavers can and should be reintroduced is a first step in successful beaver-related stream restoration. This study uses the Beaver Restoration Assessment Tool (BRAT) developed at Utah State University to model potential beaver dam densities in 63 watersheds across Colorado. The objectives of this study are to model beaver dam densities over time and space and to compare modeled densities to dams recorded in the field. Model results suggest that beaver dam densities are highest in high elevation hydrologic regions in Colorado, which include most of the ranges in the Southern Rocky Mountains. Dam capacities were historically higher, and decreases could be explained by agriculture, urbanization, and natural vegetation regime changes. Changes in BRAT densities suggest that widespread habitat degradation has decreased density but not complete destroyed beaver reintroduction potentials. Beaver reintroductions could therefore be used to restore beaver habitat, thus creating a positive feedback loop of increasing beaver capacity. In places where BRAT predicts low densities, other beaver-related restoration such as beaver dam analogs could be used to improve degraded streams and set the scene for future reintroductions. BRAT predicted densities did not strongly correlate with mapped dam densities in selected stream segments across Colorado, but disparities could be due to difficulties in comparing non-conflict capacity with actual densities. Regional scale patterns and historical magnitudes of change are likely still accurate for most of the mapped area. While BRAT highlights broad patterns and restoration potential, model output should be used as a first order approximation of suitable reintroduction locations, and future modeling and site visits should be conducted prior to restoration at any given site.